AGRICULTURAL CLIMATE RISK ZONING FOR GLADIOLUS IN SANTA CATARINA - Bosco, Leosane Cristina; Bonatto, Melina Inês; Pandolfo, Cristina; Ricce, Wilian da Silva; Stanck, Luciane Teixeira; de Souza, Alexandra Goede; Rossato, Otavio Bagiotto; Streck, Nereu Augusto (Revista Brasileira de Climatologia, 2021)
This work aims to developing an Agricultural Climate Risk Zoning for gladiolus in the State of Santa Catarina. The bioclimatic requirements and the risk criteria were defined for the crop through a bibliographic review. The probability of frost occurrence, water balance and frequency of maximum air temperatures above 34°C were calculated with meteorological database. A maximum assumed risk of 20% was considered. The period when planting is not recommended was determined for each of the development cycles (early, intermediate I and II and late). It was observed that low temperatures and occurrence of frost in autumn and winter limits gladiolus planting in the State of Santa Catarina. Analysis of the water balance indicated there is risk of water deficiency throughout the year, which varies according to the locations. Maximum air temperatures above 34ºC do not occur frequently in the State. In the Coastal regions, there are no restrictions to planting throughout the year. The Agricultural Climate Risk Zoning indicate the potential for gladiolus farming in Santa Catarina, where the greatest planting potential is in the Coastal, West and Extreme West regions.